Vive la Persistence: Engineering Human Microbiomes in the 21st Century - Katrine L. Whiteson (American Society for Microbiology, 2018)
ABSTRACT I imagine a future in which children grow up with healthy microbial communities. Engineering human microbiomes might actually be achievable in the near future, as we enter an era of hunting for human-adapted bacterial strains and phages. Furthermore, breath metabolites could allow us to track whether a probiotic colonizes persistently or a phage has knocked down a microbe of interest. Recent successes with probiotics, such as bifidobacteria that can break down human milk oligosaccharides, are making a future in which infants are intentionally colonized with health-promoting strains seem less unlikely. Viruses that infect bacteria, bacteriophages, are also important for human health both because of their role in the human microbiome and because of their potential for use in phage therapy. Monitoring the outcome of microbiome-focused interventions with breath volatile sampling is also on the horizon, which could mean real-time tracking of microbial metabolite production. Studies of early life during microbiome assembly, when the potential for effective interventions to reduce disease risk is greatest, are essential.